Transforming a young life: grade 5 Schwab osteotomy for a child with congenital kyphoscoliosis with rare T12 hemivertebra - Gul, Imran F; Mohamed Ramlee, Fadzrul Abbas; Harun, Mohd Hezery; Lim, Teck Siang (Springer, 2024)
Kyphoscoliosis is a spinal disorder where the spine’s natural curvature is abnormally altered in multiple planes. It may be associated with the presence of a hemivertebrae, as discussed in this case. Negligence of this deformity may cause symptoms of back pain, worsening spinal deformity leading to reduced lung expansion, or neurological deficit impacting the quality of life for the worse. The aim of surgery is to correct the spinal deformity. In this case, a Schwab Grade 5 osteotomy was performed along with instrumentation and fusion of the adjacent vertebrae. It is important that thorough preoperative planning is performed before the surgery, as complications may arise from the Schwab Grade 5 osteotomy procedure resulting in lifelong disability. Refined osteotomy techniques could be explored to reduce the risk of surgical complications in the near future.